41.5k views
3 votes
Answer the following two questions. What is the main difference between the two?

(8x – 3) + 2(3x + 1)





(8x – 3) – 2(3x + 1)

1 Answer

2 votes

Explanation:

i) 8x - 3 + 2(3x + 1)

=> 8x - 3 + 6x + 2

=> 14x - 1

ii) 8x - 3 - 2(3x + 1)

=> 8x - 3 - 6x - 2

=> 2x - 5

THE MAIN DIFFERENCE BETWEEN (i) & (ii) :- SIGNS ARE DIFFERENT. In (i) , there's a + sign in between (8x - 3) & 2(3x + 1) ..... but in (ii) , there's a - sign in between (8x - 3) & 2(3x + 1).

THE SIMILARITIES BETWEEN (i) & (ii) ARE (8x - 3) & 2(3x + 1).

User Suezy
by
6.6k points